(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To quantitatively describe femoral and tibial tunnel positions after anterior cruciate ligament (ACL) reconstruction using 3D computed tomography (3D CT). Subjects and methods: A cross-sectional descriptive study was conducted on 34 patients undergoing primary ACL reconstruction using the All-inside technique. Postoperative 3D CT images were used to identify tunnel center positions. The femoral tunnel position was measured using the quadrant method with depth (t%) and height (h%) coordinates, while the tibial tunnel was evaluated using anterior-posterior (AP%) and medial-lateral (ML%) coordinates. Measured values were compared with published anatomical references. Results: The mean femoral tunnel position was 31.1 ± 0.7% (t%) and 35.5 ± 1.4% (h%). Both were within the anatomical range but showed statistically significant differences from reference values (p < 0.05). The mean tibial tunnel position was 41.4 ± 1.2% (AP) and 47.9 ± 0.5% (ML), also within the anatomical range. The AP coordinate showed no significant difference (p = 0.393), while the ML coordinate differed significantly (p < 0.001). The proportion of tunnels within the anatomical footprint was 52.9% for the femur and 82.4% for the tibia. Femoral tunnel deviations were mainly anterior (23.5%) and inferior (23.5%), while tibial tunnel deviations were mainly medial (11.8%) and posterior (5.9%). Conclusion: Most tunnels were located within the anatomical footprint, but a notable proportion, especially in the femur, did not reach the optimal position. These findings suggest that reliance on anatomical landmarks alone may not ensure accuracy, and adjustments in tunnel positioning technique are needed. 3D CT provides quantitative assessment and may improve accuracy in anatomical ACL reconstruction.